Preparation and characterization of bioceramic nanocomposites based on hydroxyapatite (HA) and carboxymethyl cellulose (CMC) - Kumar, Annamalai Pratheep; Mohaideen, Kamal Khaja; Alariqi, Sameh A. S.; Singh, Raj Pal (Macromolecular Research, 2010)
We report the synthesis of biomimetic nanocomposites based on carboxymethyl cellulose (CMC) and hydroxyapatite (HA) nanoparticles via a co-precipitation method. Physico-chemical characterization was performed before and after calcination by Fourier transform infrared (FTIR) spectroscopy, solid state (31)P nuclear magnetic resonance (NMR) spectroscopy, and thermogravimetric analysis (TGA). The formation of nanocomposites was observed by wide angle X-ray diffraction (WAXD), scanning electron microscopy (SEM) with energy dispersive X-ray analysis (EDX), and transmission electron microscopy (TEM). The spectral and crystallographic data indicated the formation of hydroxyapatite in the presence of CMC. They were observed as aggregates of HA nanoparticles and CMC, whose sizes were approximately similar to 260 +/- 40 nm. The crystallite size of the hydroxyapatite particles decreased (with 2 wt% 18 +/- 3 nm) with increasing CMC content. The morphological aspects of the calcined samples revealed the sintering ability of HA nanoparticles. Nanocomposites of hydroxyapatite nanoparticles that mimic the process of nucleation and growth in nature can be prepared using biomacromolecules such as CMC.
Keywords: biopolymer; cellulose; hydroxyapatite; Nanoparticles; Particle size; X-ray diffraction

Influence of initial particle size on the magnetostriction of sintered cobalt ferrite derived from nanocrystalline powders - Mohaideen, Kamal Khaja; Joy, Pattayil Alias (Journal of Magnetism and Magnetic Materials, 2013)
The role of initial particle size on the magnetostriction coefficient of sintered cobalt ferrite derived from nanocrystalline powders is studied. Nanoparticles of cobalt ferrite with different sizes in the range 3-80 nm are synthesized by an autocombustion method using metal nitrates and glycine. It has been observed that the initial particle size of the starting powders has a strong influence on the magnetostrictive behavior of sintered cobalt ferrite. Highest magnetostrictive strain and strain derivative are obtained for sintered ferrite derived from nanoparticles of size < 5 nm. The results show that higher magnetostriction coefficient for sintered cobalt ferrite can be achieved by compacting nanocrystalline particles of very small size. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Cobalt ferrite; magnetic properties; Magnetostriction; Microstructure; Nanocrystalline; Particle size